Moments of renewal - alternative ways of viewing Indonesian cinema / David Hanan - Hanan, David (UPENA, 2008)
This paper aims to set out a number of considerations regarding the study of Indonesian cinema in the period since independence from the Dutch at the end of 1949. In particular it aims to suggest some frameworks beyond those that are found in most of the major books written on the topic, whether in English or in Indonesian. The aim is not to criticise work already done, so much as to suggest areas where work has not yet been done, and might valuably be undertaken. While clearly there are gaps in the writing about Indonesian cinema by Indonesians, there are many things that are understood about Indonesian cinema in Indonesia, perhaps even taken for granted, but not comprehended outside Indonesia.